3D printing of highly conductive silver architectures enabled to sinter at low temperatures. Issue 38 (20th September 2019) - Kim, Jung Hyun; Lee, Sanghyeon; Wajahat, Muhammad; Ahn, Jinhyuck; Pyo, Jaeyeon; Chang, Won Suk; Seol, Seung Kwon
Abstract : Highly conductive 3D Ag architectures are realized by extrusion-based 3D printing using Ag inks enabled to sinter at low temperatures. Abstract : Silver (Ag) nanoparticle-based inks are frequently used in printed electronics to form conductive patterns, but often require high-temperature sintering to achieve the optimum electrical conductivity, hindering their use in substrates with poor heat resistance. Herein, a three-dimensional (3D) printing strategy to produce highly conductive Ag 3D architectures that can be sintered at low temperatures is reported. This strategy is based on the additive deposition of Ag nanoparticles and microflakes via extrusion-based 3D printing with the Ag ink that involves poly(acrylic acid) (PAA)-stabilized Ag nanoparticles, Ag microflakes, and NaCl – a destabilizing agent. The designed Ag inks are stable and suitable for ink-extrusion 3D printing. In chemical sintering, Cl − can detach PAA from the Ag nanoparticle surface, enabling nanoparticle coalescence and sintering. An elevated annealing temperature induces increased NaCl density in the printed patterns and accelerates the surface and grain boundary diffusion of Ag atoms, contributing to enhance chemical sintering. On annealing at ∼110 °C for 30 min, the printed structures exhibited an electrical conductivity of ∼9.72 × 10 4 S cm −1, which is ∼15.6% of that of bulk Ag. Complicated Ag architectures with diverse shapes were successfully fabricated on polymeric substrates. Several structural electronic applications were demonstrated by hybrid 3D printing combining our extrusion-based 3D printing and conventional fused deposition modeling (FDM).